Kinetin induces chromosomal abnormalities in African Blue Lily (Agapanthus praecox ssp. minimus) grown in In Vitro - Jamilah Syafawati Yaacob,; Rosna Mat Taha, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Kinetin has been reported to exert inhibitory effect when used in tissue culture and in some cases reverse the action of auxin and cause growth inhibition and retardation of root formations. Kinetin also acts as ‘mitotic poison’, mimicking the effect of pesticides and toxic chemicals and interferes in mitosis mechanism of plants. The effect of kinetin on size of cell and nucleus as well as chromosome behaviour in root tip meristems of Agapanthus praecox ssp. minimus was studied. The results showed that prolong exposure to kinetin caused chromosome abnormalities to occur more frequently. Chromosome breakage yielded fragmented chromosomes, while abnormal spindle fibers caused delay in chromosome movement, termed as laggard chromosomes. Abnormal nucleus was also observed with kinetin treatments, such as micronucleus, binucleated and tripolar cells.